WAHYU DALAM ALUK MAPPURONDO: Studi Cross-Textual Reading terhadap Kisah Masuknya Injil di Buntu Malangka’ dan Kisah Kornelius sebagai Kritik Terhadap Label To Malillim - Saputra, Jefri Andri (Institut Agama Kristen Negeri Toraja, 2022)
Abstract: “Wahyu dalam Aluk Mappurondo” is the author's critique which is motivated by concern about the stereotypes that develop among Christians against Aluk Mappurondo. The stereotype in question is the label